Enhancing the Global Competitiveness of Lombok Tourism Polytechnic Students through Basic Mandarin Training - Pawestri, Setyaning; Apgrianto, Kurniawan; Melani, Boniesta Zulandha; Herayana, Desi; Suryaningsih, Hartati; Naufal Nanda Fiandra (Universitas Mataram, 2025)
Basic Mandarin Training for Tourism for Lombok Tourism Polytechnic students was held on Tuesday, May 6, 2025. This community service program, organized by University of Mataram's Language Academic Support Unit, aimed to introduce Mandarin to students. Participants were students who would be undertaking internships in the hotel industry in Taiwan. The training consisted of two stages: program socialization and the training sessions themselves. The material provided covered Mandarin phonetic basics, Hanzi character writing, and simulation-based conversation practice. Participants learned through role-playing activities in tourism scenarios, such as hotel room bookings and restaurant services. Despite the program's limited duration, participants showed high enthusiasm and actively participated. They were also introduced to using the Pleco application as a tool to support independent learning. Evaluation results indicated that this program was quite effective in providing a basic understanding of Mandarin for Lombok Tourism Polytechnic students, though independent practice in pronunciation is highly needed. Therefore, after the training, participants were advised to integrate applications and AI to support their self-study efforts. With improved Mandarin skills, students are expected to compete in the global tourism industry and provide higher-quality services to Chinese tourists.